(untitled) (Itinera, 2017)
This paper aims to investigate the ways in which the wine was represented in the Italian cinema, through some exemplary movies chosen from particularly representative genres: such as neorealism, the Italian comedy and authorâs cinema. Our analysis will show that the wine tasting, in the Italian cinema, has managed very well symbolize, from time to time: conviviality, individual memory, differences of class, sex, death, and finally, the sacred and the religious.Â